Two Circumpolar Ground Beetle Species (Coleoptera: Carabidae) Were in Hokkaido, Japan, Late in the Last Glacial Period - Shigehiko Shiyake (Quaternary)
Fossilized body parts of two cold-adapted ground beetle species, Elaphrus lapponicus and Diacheila polita, were identified from a deposit dated to the Late Glacial period in Hokkaido, Japan. The paleoenvironmental reconstruction presented here has been based on modern temperature ranges and environmental conditions, along with paleobotanical evidence from the site. Late Glacial temperatures were at least 6 degrees °C lower than modern temperatures in summer, and the area around the site was mostly covered with forest tundra, which exists only in areas further north than Hokkaido.